Order Submission Strategy and the Curious Case of Marketable Limit Orders - Peterson, Mark; Sirri, Erik (Journal of Financial and Quantitative Analysis, 2002)
We provide empirical evidence on order submission strategy of investors with similar com-mitments to trade by comparing the execution costs of market orders and marketable limit orders (i.e., limit orders with the same trading priority as market orders). The results in-dicate the unconditional trading costs of marketable limit orders are significantly greater than market orders. We attribute the difference in costs to a selection bias and provide evidence suggesting the order submission strategy decision is based on prevailing market conditions and stock characteristics. After correcting for the selection bias, the results show the average trader chooses the order type with lower conditional trading costs. I.